Treated polystyrene microcarriers vero cells using ultraviolet/ozone (UVO) expansion of serum-free medium adapted - Judy, Wong (2018)
Cell culture refers to a process by which cells are removed from an animal and grown in an artificial environment. The field of cell culture is becoming increasingly important over the years especially from the point of commercial values. Many cell lines have been used for the production of many biological products as well as for a variety of research studies. Among these cell lines are Vero cell which is derived from the kidney of African green monkey. A lot of vaccines available in market today are prepared using Vero cells as substrate. In addition, Vero also has been widely used in many virology, cancer and also toxicological studies. Traditionally, Vero cells are cultured using medium that are supplemented with serum. The use of serum however has many drawbacks as it may increase the risk of contamination, has high batch to batch variability, increase the cost of culturing, interferes with the purification of cell culture products etc. In this experiment, experiments were carried out with the aim to overcome these problems by adapting Vero cells into serum-free medium. Adaptation were carried out sequentially from 100% serum supplemented medium (SSM) to 100% serum-free medium (SFM). In each adaptation, the percentage of SSM in culture medium was reduced by 25% while SFM percentage was increased by 25%. Another objective of this experiment was to upscale the culture of Vero cells from T-flask to spinner vessel. Vero cells that have been adapted to 100% SFM were grown in spinner vessel using ultraviolet/ozone (UVO) treated polystyrene (PS) microcarriers. Results from experiments revealed that, Vero cells were successfully adapted to 100% SFM with higher peak cell concentration and shorter doubling time when compared to culture of Vero cells in 100% SSM. Further, Vero cells also have been successfully cultured in spinner vessel by using low cost UVO treated PS microcarriers that have been self-prepared in the laboratory.